Photoluminescence and First-principle Calculations of the Single Vacancy in Diamond - Kaiyue WANG; Wenjin ZHANG (Medžiagotyra, 2022)
The isolated single vacancy is one of the most common defects in diamond, while it is of considerable interest and importance that significantly influences the optical properties of diamond. Although a number of literature publications about the electron structure and density states of single vacancy in diamond from the density functional theory (DFT) calculations, these results are very difficult to be identified from the perspective of experiments. In this paper, the low-temperature photoluminescence (PL) technology was employed to study the emission properties of single vacancy in diamond, and then the photoionization energy, migration energy and vibrionic structure obtained from PL experiments were compared with these obtained from the first-principle calculations. Results showed that the calculation results agreed well with the PL results for the neutral vacancy while differed for the negatively charged vacancy, indicating that for ultrapure diamond, the vacancy mainly existed in form of the neutral rather than the negatively charged.